In the zone or out of bounds? How sports and physical activity anxiety affects life satisfaction among students - Mancera, Marlon A.; Sumera, Eduard S.; Tagare, Jr., Ruben L.; Lopez, Gilbert E.; Orgeta, Irish M.; Haji Kasan, Yashier T.; Cristobal, Harold Deo; Aton, Armand G.; Adlaon, Gauvin (Institute of Advanced Engineering and Science, 2025)
This study aims to explore the relationship between sports and physical anxiety and life satisfaction among college students in a leading Philippine state university. Employing a quantitative research design, specifically descriptive correlation, data were collected from 2,043 respondents using simple random sampling. The research utilized the physical activity and sport anxiety scale and the life satisfaction index to measure the respective constructs, with analyses conducted using Spearman’s rho correlation coefficient to assess relationships between variables. Results indicated a significant relationship between sports and physical anxiety and life satisfaction, revealing that higher levels of anxiety corresponded to lower life satisfaction. These findings highlight the importance of addressing sports and physical anxiety to improve overall well-being. Implications suggest that institutions should implement mental health and wellness initiatives aimed at reducing anxiety and promoting supportive environments in physical education settings. By fostering a culture that prioritizes psychological well-being alongside physical engagement, institutions can enhance students’ life satisfaction and overall quality of life.